Investigation of Preventive Practices and Perception of Cervical Cancer Among Female Students at the Polytechnic in Ibadan, Oyo State - Ayinde Abayomi Oluwasegun; Aibinuomo Ayomide Oluwaseyi; Layemo Princewill Adeoye; Agbobavbare Omotunde; Akinfoyeku Sunday; Oni Shalom Oluwajomiloju; Akinoye John Iyanu (PT. Antis International Publisher, 2024)
The objective of this study is to determine the perception of female students of the polytechnic of Ibadan, Oyo State, towards cervical cancer and preventive. A cross-sectional study design was used to determine the above objective. The survey included 429 female students who lived on the Polytechnic Ibadan campus. A systematic sampling technique was used to choose 210 rooms out of a total of 420 rooms, and all of the selected rooms' occupants were questioned under the premise that there were two people in each room. Data were gathered using a self-administered questionnaire that had been pretested. Respondents with one or more risk factors were classified as being at a higher risk for cervical cancer and those with no risk factors as being at a lower risk. Data was analyzed using descriptive statistics and Chi square test at p<0.05. Mean age of respondents was 24.2±3.7 years. More than half (60.3%) had good knowledge about cervical cancer and 55.1% had a good perception of cervical cancer. The identified risk factors were sexual debut before the age of 18 years (25.1%) multiple sexual partnering (11.6%), unprotected sexual intercourse (59.2%) and positive family history of cervical cancer (2.2%). Majority of the respondents (96.9%) were at a higher risk for developing cervical cancer. Few respondents (8.0%) had ever heard of the pap smear test and the major sources of information were the internet (33.3%) and hospital (25%). The uptake of pap smear test was low (1.8%). Majority of the respondents (71.9%) were not aware of where the pap smear test could be done. Only 4.7% were willing to receive the human papilloma virus (HPV) vaccine, while 5.1% were willing to do a pap smear test. The major reasons cited for not wanting to do the pap smear test was lack of perceived need for the test (13.4%) and financial constraint (1.5%). Respondents who were 25 years and below and single were more likely to have a good perception of cervical cancer. Those aged <30 years (OR 1.39, 95% CI 0.34-5.66), single (OR 1.07, 95% CI 0.45-2.50), those from faculty of science (OR 1.22, 95% CI 0.57-2.58) and those that had low risk score (OR 2.66, 95% CI 0.54-12.98) were likely to have a good perception of cervical cancer. Even though respondents had a fair amount of awareness about cervical cancer, they nevertheless exhibited significant behavioral risk factors for the condition. The pap smear test had very poor awareness and uptake. Therefore, it is necessary to develop health communication initiatives that would motivate tertiary students to apply their learning to prevent cervical cancer